Identifikasi Permasalahan Kios Kosong Pada Shopping Center Strata Title Di Kota Palembang (Studi Kasus : Palembang Trade Center – PTC) - Raden Ahmad Nur Ali (Jurnal Tekno Global, 2021)
Shopping center strata is a new model of property retail that has developed due to a bad investment climate, so that investors are more interested in short term investment and influence the shopping center model which develops into a strata title form. From Various Literatures of shopping centre is a form single property model. This is intended to facilitate management to manage freely according to existing theorie. The existing shopping centre model adopts a grid layout design pattern, because this pattern can result in small and large units. And applying a grid pattern to the layout creates a non-strategic position, so that visitors are rarely traversed and it affects the low occupancy rate of units or Empty Stall.  The Focus of this research is to find a correlation between the vacancies of stalls in the shopping center strata and the layout. PTC Mall is one of Shopping Centers in Palembang City, the choice PTC Mall Because its location which is close to dense settlements and faar from other shopping centers in Palembang City. So that it can answer my hypothesis about Occupancy rate in shopping center strata due to the position of a non strategic and strengthened by teh nature of strata ownership should not be applicable to shopping centers. After observations, it was found that the layout design, likes placement of the entrance, the placement of the escalator, the placement of the anchor tenants did not form, causing the spread of visitors and became empty stalls.  Keyword : layout, shopping center, occupancy rate, empty stall